2013
DOI: 10.1186/1471-2377-13-167
|View full text |Cite
|
Sign up to set email alerts
|

Low contrast visual acuity testing is associated with cognitive performance in multiple sclerosis: a cross-sectional pilot study

Abstract: BackgroundCognitive impairment and visual deterioration are two key clinical symptoms in MS and affect 50 to 80% of patients. Little is known about the influence of cognitive impairment on visual tests recommended for MS such as low contrast sensitivity testing. Our objective was to investigate whether low contrast sensitivity testing is influenced by cognitive impairment in multiple sclerosis (MS) patients.MethodsCross-sectional study including 89 patients with relapsing-remitting MS. All patients received co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 48 publications
4
30
2
Order By: Relevance
“…Evaluation of verbal memory in MS patients supported a main deficit in information retrieval, followed by encoding as disability increased, with infrequent storage deficit [41]. Visual acuity could affect the performance on RCFT and further interpret lower visual memory scores; however, our patients reported adequate visual acuity and visual performance was more related to information processing tests (with no significant differences between OCB subgroups in our study) and to a lesser degree to memory [42]. Very recently, a positive association between visuospatial memory and glutamate levels in the hippocampal, thalamic and cingulate regions has been detected in MS patients, but not in healthy participants [43].…”
Section: Discussioncontrasting
confidence: 64%
“…Evaluation of verbal memory in MS patients supported a main deficit in information retrieval, followed by encoding as disability increased, with infrequent storage deficit [41]. Visual acuity could affect the performance on RCFT and further interpret lower visual memory scores; however, our patients reported adequate visual acuity and visual performance was more related to information processing tests (with no significant differences between OCB subgroups in our study) and to a lesser degree to memory [42]. Very recently, a positive association between visuospatial memory and glutamate levels in the hippocampal, thalamic and cingulate regions has been detected in MS patients, but not in healthy participants [43].…”
Section: Discussioncontrasting
confidence: 64%
“…A fMRI study with a go/no‐go response discrimination task detected an increased activation of the precuneus, the posterior part of the cingulum and the insular cortex in MS patients compared to healthy controls (Loitfelder et al., 2014). Previous studies provided already evidence for an association between OCT outcomes, visual function, and neuropsychological measurements (Toledo & Sepulcre, 2008; Wieder et al., 2013). In our small subgroup of patients with a neuropsychological assessment, we performed an explorative post hoc analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Investigating focal cortical volume patterns might help to identify regions that are important hubs in functional or structural networks and might contribute to the disability of MS patients. Previous studies indicated, that impairment of visual function might be as well associated with cognitive function in MS (Toledo et al., 2008; Wieder et al., 2013). The purpose of this study was to investigate to what extent OCT measures correlate with cortical areas that are not part of the primary visual system, and to explore if there is a distinctive pattern of association with cortical regions and if these associations might be linked to neuropsychological performance.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Letter acuity charts typically use high contrast optotypes, but charts using low contrast letters have also been developed and have been shown to be useful in measuring visual deficits in a variety of disease states. [24][25][26] There has been no previous study of the slope of the psychometric function for low-contrast visual acuity charts. There are a number of reasons to expect that Probit Size will typically be larger (i.e.…”
Section: Introductionmentioning
confidence: 99%